Answer :

I'm assuming you meant to write a^4 = 625.

If that is the case, then note how 625 = 25^2, and how a^4 is the same as (a^2)^2

So we go from this

a^4 = 625

to this

(a^2)^2 = 25^2

Apply the square root to both sides and you'll end up with: a^2 = 25

From here, apply the square root again to end up with the final answer: a = 5 or a = -5

As a check:

a^4 = (-5)^4 = (-5)*(-5)*(-5)*(-5) = 25*25 = 625

a^4 = (5)^4 = (5)*(5)*(5)*(5) = 25*25 = 625

Both values of 'a' work out

Other Questions